Effect of α-dl tocopherol acetate (antioxidant) enriched edible coating on the physicochemical, functional properties and shelf life of minimally processed carrots (Daucus carota subsp. sativus) - Keshari, Divya; Tripathi, Abhishek Dutt; Agarwal, Aparna; Rai, Saloni; Srivastava, Suresh Kumar; Kumar, Pankaj (Elsevier B.V., 2022)
The present study was carried out to investigate the effect of varying sodium alginate-based edible coating (1, 2, and 3 %, w/v) supplemented with α- tocopherol acetate (antioxidant) at different concentrations (0.5 and 1 % w/v) on minimally processed carrot slices during 15 d storage at 10 °C and 65 % relative humidity. Seven different formulations (T1- T7) comprising different alginate and antioxidant combination were tested for selecting the best formulation maintaining the physicochemical attributes, antioxidant potential, carotenoid content, and overall acceptability (microbial counts) of carrot slices. Treatment T4 (2% sodium alginate + 1% α-tocopherol acetate) served as the best formulation in maintaining the quality, acceptability, nutritive value of minimally processed carrots. The T4 treated carrot samples showed minimum variation in weight loss, TSS, pH, whiteness index, reducing sugar, ascorbic acid content, TPC, antioxidant activity, total carotenoids, total aerobic bacterial count and yeast and mold counts, respectively in comparison to other treatments during storage. The statistical analysis also confirmed the significant (p<0.05) variation in physicochemical properties, antioxidant potential, carotenoid content and microbial count in control samples than edible coating formulations during storage.
This paper is submitted by the author of IIT (BHU), Varanasi, India
Keywords: Effect of α-dl tocopherol acetate; physicochemical; Shelf life extension; Minimally processed carrots; Functional properties; Antioxidant; Edible coating